Coping, Positive Growth and Social Support in Turkish Women with Breast Cancer - Gülşen Filazoğlu Çokluk (Sakarya Üniversitesi Kadın Araştırmaları Dergisi)
The study aimed to explore the role of social support, coping strategies in fostering positive growth among Turkish women with breast cancer, utilizing a cross-sectional design. Involving 188 women from three hospital centers in Türkiye the research employed standardized measures such as The Ways of Coping Inventory and the Stress Related Growth Scale, alongside collecting socio-demographic and medical information. The results revealed significant positive correlations between social support, problem-solving, religious coping, and seeking social support coping strategies with positive growth (ps < 0.05). Conversely, helplessness coping strategies were inversely correlated with positive growth (ps < 0.05). Furthermore, multivariate analysis indicated that 61.2% of the positive growth score could be attributed to variables such as the stage of cancer, marital status, social support, problem-solving coping, and religious coping. The perceived availability of emotional support, particularly in the context of benefit finding, plays a crucial role in the patients' emotional adjustment. Conclusively, the findings suggest that enhancing social support, problem-solving, and religious coping could significantly improve the outcomes for Turkish women dealing with breast cancer. This research underscores the need for improvements in healthcare policies, support systems, and educational programs, proposing that such interventions should be integrated into healthcare services to effectively contribute to the positive growth of breast cancer patients.